Förvaltningsarbete för mångfald och konkurrens - Sara Irisdotter Aldenmyr (Educare)
This article reflects on the possibility to promote diversity in Swedish schools. Our municipal authorities are responsible of managing schools financially as well as promoting diversity and equality. Thus, several critical researchers claim that the marketization of the educational sphere, including students’ freedom of choice, leads to segregation and discrimination. There are also theorists who claim the opposite by pointing out that the free market represents democratic values and promotes diversity. The aim of this article is to study how administrators of the municipal authorities reflect on their possibility to promote diversity within a marketized school system. The material consists of four interviews with head administrators of municipal authorities. The results partly confirm the clash between competition, freedom of choice and diversity. Yet, the municipal administrators seem to believe in the possibility to further the progress of diversity within the marketized school.